Use of aqueous dispersions of two-phase emulsion graft copolymers as binders for stiffening materials in the textile and leather industry - SCHWEMMER; MONIKA; KOEGLER; GERHARD; KOHLHAMMER; KLAUS (1997)
PCT No. PCT/EP94/03721 Sec. 371 Date Apr. 17, 1996 Sec. 102(e) Date Apr. 17, 1996 PCT Filed Nov. 10, 1994 PCT Pub. No. WO95/13418 PCT Pub. Date May 18, 1995Process for the stiffening of textile or leather materials, includes (a) applying an aqueous polymer dispersion to a textile structure on the basis of a woven or nonwoven fabric, or a leather material; (b) drying the textile structure or leather material; and (c) the stiffening material thus produced is deformed and glued with the textile and leather material to be stiffened, in which an aqueous dispersion of a two-phase, sealable emulsion graft copolymer having a soft phase and a hard phase is applied. The hard phase has a glass transition temperature of Tg of at least 50 DEG C. and includes monomer units such as methyl methacrylate, styrene, diisopropyl fumarate and vinyl chloride. The soft phase has a glass transition temperature Tg of at least 30 DEG C. lower than the Tg of the hard phase, and the soft phase has monomer units such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, vinyl acetate, vinyl propionate, isopropenyl acetate, vinyl laurate, vinyl esters of saturated, alpha -branched monocarboxylic acids having 9 to 10 carbon atoms, ethylene, propylene or 1,3-butadiene.